The effects of mathematical ability and motivational beliefs on students’ perceptions of feedback usefulness - Söderström, Sharmin; Palm, Torulf; Granberg, Carina (Frontiers in Education, 2024)
Research has shown that students' learning gains in mathematics are greater when they work with problems rather than routine tasks. These learning gains from problem-solving activities may be enhanced by providing feedback that does not give away the solutions to the problems, but helps students construct their solution methods themselves and anchor their reasoning in intrinsic properties of the mathematical components involved in the reasoning.However, in order to use feedback, students would need to perceive it as useful, and not all students may find such feedback useful. In this study, we investigate how students' ability and motivational beliefs affect how useful they perceive feedback aimed at supporting mathematical reasoning to be. In the study, students worked with mathematical problems and received metacognitive and heuristic feedback when they needed help. We used structural equation modelling (SEM) to analyze the effects. The results show that students' mastery goals had a direct effect on the perceived usefulness of the feedback, but no such effects were found for students' national test grades, self-efficacy beliefs, performance goals, or intrinsic or extrinsic forms of motivation. The proportion of successful use of feedback did not mediate the effects.